Peroxisome Proliferator-Activated Receptor Deficiency Increases the Risk of Maternal Abortion and Neonatal Mortality in Murine Pregnancy with or without Diabetes Mellitus: Modulation of T Cell Differentiation - YESSOUFOU, AKADIRI; Hichami, Aziz; BESNARD, Phillipe; MOUTAIROU, KABIROU; Khan, Naim Akhtar (My University, 2006)
We assessed the implication of peroxisome proliferator-activated receptor (PPAR) deficiency in pregnancy outcome and neonatal survival and in the modulation of T cell differentiation in murine diabetic pregnancy and their offspring. Pregnant wild-type (WT) and PPAR-null mice of C57BL/6J genetic background were rendered diabetic by five low doses of streptozotocin. We observed that, in the absence of diabetes, PPAR deficiency resulted in an increase in abortion rate, i.e. 0% in WT mice vs. 20% in PPAR-null mice [odds ratio (OR) 14.33; P 0.013]. Under diabetic conditions, the abortion rate was enhanced, i.e. 8.3% in WT mice vs. 50% in PPAR- null mice (OR 4.28; P 0.011). In the pups born to diabetic dams, the offspring mortality, due to the absence of PPAR, was enhanced, i.e. 27.7% in WT mice vs. 78.9% in PPAR-null animals (OR 11.48; P < 0.001). Moreover, we observed that T helper (Th) 1/Th2 balance was shifted to a pregnancy protecting Th2 phenotype in WT diabetic dams and to a noxious Th1 phenotype in PPAR-null mice with diabetic pregnancy. Furthermore, offspring born to diabetic WT dams were hyperinsulinemic and hyperglycemic, and they exhibited upregulated profile of Th2 cytokines, whereas those born to diabetic PPAR-null dams were hypoinsulinemic and hyperglycemic, and they showed down-regulated profile of Th2 cytokines. However, IFN-, a Th1 cytokine, was up-regulated in the offspring of both diabetic WT and PPAR-null dams. Altogether, our results suggest that PPAR deficiency in mice may be implicated in the increase in maternal abortion, neonatal mortality, and T cell differentiation.
Keywords: PPARα; diabetic pregnancy; Th1/Th2 phenotype; mice